2008
DOI: 10.1111/j.1755-0998.2008.02188.x
|View full text |Cite
|
Sign up to set email alerts
|

Polymerase chain reaction‐based detection of Fusarium circinatum, the causal agent of pitch canker disease

Abstract: Pitch canker is a highly damaging disease of Pinus radiata and the New Zealand forest industry is concerned by the potential impact of the disease, should it arrive, in New Zealand. To provide a rapid identification technique for this pathogen, a polymerase chain reaction-based diagnostic method has been developed. The method is able to detect the presence of the pathogen within infected host tissue, as well as infested soil and the reliability of the test has been estimated using Bayesian statistics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 16 publications
0
15
0
Order By: Relevance
“…Of these, PCR-based methods using specific probes and primers allow for the simultaneous detection and quantification of the pathogen, especially when combined with quantitative real-time PCR (qPCR). Due to their sensitivity, these methods can be used to detect and quantify F. circinatum contamination in seed lots (Ioos et al 2009;Dreaden et al 2012) or to detect the pathogen in infected plant material (Schweigkofler et al 2004;Ramsfield et al 2008). These qPCR-based methods can also be used to obtain epidemiological data by, for example, quantifying the airborne conidia of F. circinatum associated with pitch canker outbreaks (Schweigkofler et al 2004;Garbelotto et al 2008).…”
Section: Culture-independent Detection and Quantification Of Fusariummentioning
confidence: 99%
“…Of these, PCR-based methods using specific probes and primers allow for the simultaneous detection and quantification of the pathogen, especially when combined with quantitative real-time PCR (qPCR). Due to their sensitivity, these methods can be used to detect and quantify F. circinatum contamination in seed lots (Ioos et al 2009;Dreaden et al 2012) or to detect the pathogen in infected plant material (Schweigkofler et al 2004;Ramsfield et al 2008). These qPCR-based methods can also be used to obtain epidemiological data by, for example, quantifying the airborne conidia of F. circinatum associated with pitch canker outbreaks (Schweigkofler et al 2004;Garbelotto et al 2008).…”
Section: Culture-independent Detection and Quantification Of Fusariummentioning
confidence: 99%
“…What is the performance of the test method? (if used) Very specific and effective molecular methods have been developed for Gibberella circinata identification on samples analysed in laboratory and even for direct detection in planta (Perez-Sierra et al 2007, Ramsfield et al 2008, Ioos et al 2009). DNA analysis method is quite reliable (without false positive or negative).…”
Section: Perseus Final Project Reportmentioning
confidence: 99%
“…A detailed characterization of pitch canker fungus isolates using PCR-RFLP analysis was used to confirm the establishment of the pathogen in Chile (Jacobs et al, 2007) and in Spain (Perez-Sierra et al, 2007), where mating types showing virulence differences were identified by multiplex PCR. As pitch canker could be a threat for the New Zealand forest industry, a PCR-based diagnostic method was developed to detect the pathogen within infected host tissues and in infested soil (Ramsfield et al, 2008).…”
Section: Detection and Monitoringmentioning
confidence: 99%